Cover Feature: Fluorescent Turn‐On Probes for the Development of Binding and Hydrolytic Activity Assays for mRNA Cap‐Recognizing Proteins (Chem. Eur. J. 27/2019). Issue 27 (4th April 2019) - Kasprzyk, Renata; Starek, Beata J.; Ciechanowicz, Sylwia; Kubacka, Dorota; Kowalska, Joanna; Jemielity, Jacek
Abstract : 7‐Methylguanine nucleotides labelled with pyrene were found to behave as sensitive turn‐on probes upon enzymatic cleavage or binding to specific proteins. This observation served as the basis for developing binding‐ and hydrolytic‐activity assays in a 96‐well format for two therapeutically‐relevant 7‐methylguanosine cap recognising proteins: translation initiation factor (eIF4E) and decapping enzyme (DcpS). A complex of eIF4E with pyrene labelled nucleotide is depicted on the cover. More information can be found in the Full Paper by J. Kowalska, J. Jemielity, et al. on page 6728 .